2020
DOI: 10.3390/nu12071928
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Timing of a Leucine-Enriched Amino Acid Supplement on Body Composition and Physical Function in Stroke Patients: A Randomized Controlled Trial

Abstract: The combination of exercise and nutritional intervention is widely used for stroke patients, as well as frail or sarcopenic older persons. As previously shown, supplemental branched chain amino acids (BCAAs) or protein to gain muscle mass has usually been given just after exercise. This study investigated the effect of the timing of supplemental BCAAs with exercise intervention on physical function in stroke patients. The participants were randomly assigned to two groups based on the timing of suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
10
2
Order By: Relevance
“…Moreover, for surviving patients after the acute disease stage of stroke, screening frailty could help clinicians and family members make an appropriate rehabilitation program and intervention program for exercise and nutrition. A previous study suggested that a combination of exercise training and nutritional intervention with branched-chain amino acid improvements can effectively improve leg press strength and the Berg balance scale score among poststroke patients [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, for surviving patients after the acute disease stage of stroke, screening frailty could help clinicians and family members make an appropriate rehabilitation program and intervention program for exercise and nutrition. A previous study suggested that a combination of exercise training and nutritional intervention with branched-chain amino acid improvements can effectively improve leg press strength and the Berg balance scale score among poststroke patients [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both groups underwent a rehabilitation program for 2 months, with two sessions daily. Muscle mass results were similar in both groups; however, BCAA intake with breakfast was more effective for physical performance and decreasing body fat mass [ 84 ].…”
Section: Impact Of Nutritional Supplementation On Post-stroke Rehabilitationmentioning
confidence: 99%
“…The ability to perform ADLs was essential for the improvement of the quality of life for stroke patients and their families. Previous studies showed that increased nutritional or exercise interventions could improve the muscle mass, strength, and physical function of patients with sarcopenia and stroke 37,38 . Increased muscle mass was found to improve ADLs, which was important for stroke rehabilitation.…”
Section: Implications For Practicementioning
confidence: 99%